Dünya’nın Teknolojik Başarısı: Ülkelerin, Kıtaların ve Dönemlerin Güncellenmesi ve Analizi - Büşra Ağan (İzmir İktisat Dergisi, 2022)
This study examines the development of Technology Achievement Index for 72 nations from 1990 through 2019. The nations in the TAI are classified into four groups of countries and the determinants of TAI are comprised of creation of technology, diffusion of old technology, diffusion of new technology, and development of human skills for three periods of time. The main findings indicate that TAI ranking consists of leaders who are 9 countries, potential leaders are 43 countries, dynamic adopters are 5 countries, and only 5 countries are marginalized. In general, the findings show that leaders of TAI have capabilities to enable and use technology in three periods. Besides, over the past decades, the number of countries entering the ranks of potential leaders has observed an increase. Additionally, the empirical findings demonstrate that there is a statistically significant relationship between four sub-indices and has a positive correlation. This study, therefore, provides on the role of technological achievements, diffusions, and adaptions in the development of countries on the basis of four sub-indices, income levels, and time.